Auditory neglect and related disorders - Gutschalk, Alexander; Dykstra, Andrew R. (The human auditory system, 2015)
Neglect is a neurologic disorder, typically associated with lesions of the right hemisphere, in which patients are biased towards their ipsilesional - usually right - side of space while awareness for their contralesional - usually left - side is reduced or absent. Neglect is a multimodal disorder that often includes deficits in the auditory domain. Classically, auditory extinction, in which left-sided sounds that are correctly perceived in isolation are not detected in the presence of synchronous right-sided stimulation, has been considered the primary sign of auditory neglect. However, auditory extinction can also be observed after unilateral auditory cortex lesions and is thus not specific for neglect. Recent research has shown that patients with neglect are also impaired in maintaining sustained attention, on both sides, a fact that is reflected by an impairment of auditory target detection in continuous stimulation conditions. Perhaps the most impressive auditory symptom in full-blown neglect is alloacusis, in which patients mislocalize left-sided sound sources to their right, although even patients with less severe neglect still often show disturbance of auditory spatial perception, most commonly a lateralization bias towards the right. We discuss how these various disorders may be explained by a single model of neglect and review emerging interventions for patient rehabilitation.